A pilot study of twice-weekly group-based written exposure therapy for veterans in residential substance use treatment: effects on PTSD and depressive symptoms - Natalia Van Doren; Fang-Hsi Chang; Amanda Nguyen; Kevin R. McKenna; Derek D. Satre; Shannon Wiltsey-Stirman (Addiction Science & Clinical Practice)
Abstract Background Posttraumatic stress disorder (PTSD) is highly comorbid with substance use disorders (SUDs), resulting in high prevalence of PTSD among individuals in residential SUD care. However, there is limited research on integrating trauma treatment into residential SUD care settings. The aim of the present project was to conduct an initial evaluation of the effects of group-based Written Exposure Therapy (WET) on PTSD and depressive symptoms that was integrated into programming for individuals in residential SUD treatment. Methods Participants were 48 Veterans with comorbid PTSD-SUD from a 28 day residential SUD program at a Veterans Affairs Medical Center. Eligible participants were enrolled in 5 sessions of WET, delivered twice-weekly in an adapted group format. PTSD symptoms and depressive symptoms were assessed at each session with the Posttraumatic Stress Disorder Checklist, DSM-5 version (PCL-5) and the Patient Health Questionnaire (PHQ-9). Results Over 5 months, 76.2% of the target population were successfully enrolled. Of the enrolled sample, 48 participants, 92% (n = 44) completed 3 sessions, while 56% (n = 28) completed 5 sessions. Generalized Estimating Equations (GEE) showed significant within-person reductions in PTSD symptoms over time, with an average decrease of 3.18 per session (χ² = 23.21, p = .006) and moderate effect sizes (d = 0.46 and d = 0.51 at mid- and post-treatment). In addition, there were significant reductions in depressive symptoms within-persons over time, with an average per-session reduction of 1.13 (χ² = 23.10, p = .006). Conclusion Findings demonstrate that brief, group-delivered WET is feasible and shows promise for addressing PTSD and depressive symptoms in residential SUD treatment. Results of the present evaluation could inform further efficacy testing and implementation of PTSD treatment into residential SUD settings.